A Survey on Securing Cloud Service Data by Using Homomorphic Encryption - Sai krishna, J; Muni Kumar, S; Venkataramana, K (International Journal of Computer Sciences and Engineering, 2025)
In Recent trends shows Cloud computing technology is adopted by many IT companies as it reduces the investment burden for infrastructure, software, hardware or any reasonably resource in a company. However, one amongst the most important problems in implementing or adopting cloud is threats due to security breaches. To ensure security, countless ancient secret writing algorithms are used like various truthful cipher mechanisms, RSA, Homomorphic secret writing etc. however these algorithms are solely accustomed to convert plain text into cipher text during transit or at storage.Homomorphic encryption can be a particular type of encryption where mathematical operations on the cipher text is like mathematical operations on the corresponding plaintext. Homomorphic encryption (HE) is fascinating on account of the particular proven fact it can operate on big databases. In this paper discussed and studied the fundamental concepts of HE, along with various homomorphic encryption schemes andtheir possible implementation in cloud computing.